Integration of the STEM Approach in Indonesian Language Learning to Improve Elementary School Students’ Critical Thinking Skills: A Quasi-Experimental Study - Dwi Rohman Soleh; Addy Septyawan; Estuning Dewi Hapsari (Jurnal Pendidikan Terapan, 2026)
Purpose: The purpose of this study is to determine whether incorporating the Science, Technology, Engineering, and Mathematics (STEM) method into Indonesian language instruction may enhance elementary school students' critical thinking abilities. The study was carried out in response to students' poor critical thinking abilities and the underutilisation of interdisciplinary teaching methods in Indonesian language instruction. Methods: This study used a nonequivalent control group design and a quasi-experimental method in a quantitative manner. 55 primary school kids made up the participants; they were split into two groups: an experimental class (n = 28) and a control class (n = 27). Pretests and posttests of critical thinking skills, classroom observations, and documentation were used to gather data. Descriptive statistics, homogeneity and normality tests, paired-sample t-tests, and independent-sample t-tests were all used in the data analysis. Findings: The findings showed that students' critical thinking abilities were much enhanced by the use of the STEM methodology. While the independent-sample t-test revealed significantly higher posttest scores in the experimental group relative to the control group (p < 0.05), the paired-sample t-test revealed a significant difference between pretest and posttest scores in the experimental class (p < 0.05). The STEM intervention had a significant educational influence on students' critical thinking abilities, according to the computed effect size. Research implications: Because of the study's single-school context, limited sample size, and lack of random assignment, the results should be interpreted cautiously even though they show the efficacy of STEM-based Indonesian language acquisition. To improve the findings' generalisability, larger and more varied sample sizes from various educational environments should be used in future research. Originality: By incorporating the STEM approach into Indonesian language learning an area that has gotten little attention in prior research this study makes a unique addition. This study shows how STEM integration in language instruction can improve students' critical thinking abilities, in contrast to the majority of STEM studies that concentrate on science and maths.